Rice quality improvement. A review - Chanakan Prom-u-thai (2020)
© 2020, INRAE and Springer-Verlag France SAS, part of Springer Nature. The value of rice to producers and consumers can be markedly increased by grain quality improvement. However, effective increase in the economic and nutritive value of rice can only be made with a better understanding of the conditions governing the production of rice with different grain types and quality and the control of quality along the value chain. This review examines the conditions governing the production of rice with price differentiated grain types and grades, with the aim to identify the limits and opportunities for quality and value upgrading. This begins with the production of Basmati and Hom Mali, the most expensive rice on global market, followed by a review of the effectiveness of rice breeding and management, and the roles of postharvest sorting and quality control, with the following conclusions. The production of rice with the highest price and quality is restricted by the eco-geographical limits. A substantial quality improvement has been achieved within each grain type through breeding, with grain quality as the key attribute differentiating modern high-yielding rice varieties that have become mega-varieties from those that have not. Due to the general preference for unbroken rice kernels, the value of rice is increased with grain breakage reduction at harvest and postharvest. The paddy from Asia’s numerous small farms, with diverse ecological and socio-economic conditions, is required to be sorted into quality and price differentiated segments of the value chain, so providing the incentives to manage for quality. Incentives are also required for nutrient-enriched rice to be segregated from the non-enriched grain, to impact the nutrient intake of low-income rice consumers. Ambitious rice development strategies aiming to improve grain quality are effective and sustainable only with the recognition of key quality control processes, and the need for quality differentiating management along the value chain.